2017
DOI: 10.1364/ao.56.005526
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing through long period fiber gratings mechanically induced on tapered optical fibers

Abstract: In this work the feasibility of employing two well-known techniques already used on designing optical fiber sensors is explored. The first technique employed involves monomode tapered fibers, which were fabricated using a taper machine designed, built, and implemented in our laboratory. This implementation greatly reduced the costs and fabrication time allowing us to produce the desired taper length and transmission conditions. The second technique used fiber Bragg gratings, which we decided to have mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Both types of the structure are widely used in the transmission as band rejectors [35][36][37][38][39][40][41][42][43]. Such band rejectors are further developed to serve as transverse load, temperature, pressure, twist, and refractive index sensors [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Applications Of Mechanically Induced Lpfgsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both types of the structure are widely used in the transmission as band rejectors [35][36][37][38][39][40][41][42][43]. Such band rejectors are further developed to serve as transverse load, temperature, pressure, twist, and refractive index sensors [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Applications Of Mechanically Induced Lpfgsmentioning
confidence: 99%
“…The mechanically induced LPFGs also serve as temperature sensors [48][49][50], while the model of the LPFG can be formed by using 3D printing techniques in the fabrication process [51]. In 2011, L. A. García-de-la-Rosa et al [52] reported the spectral response of a mechanically induced LPFG to the ambient temperature variation.…”
Section: Applications Of Mechanically Induced Lpfgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalization can improve the sensor sensitivity [ 81 ]: a 25-points 100 μm period MF LPG was inscribed with a UV laser on top of a PMMA coated 5.4 μm diameter MF and was used to measure temperature from 20 °C to 50 °C providing S ~ 385.11 pm/°C. LPG can be also induced mechanically in MF [ 82 ]. A 5-cm long aluminum plate with 500 μm-period and 300 μm grooves was placed under a 60 μm MF ( Figure 15 c): by applying heat to the periodic groove plate, this structure exhibited S ~ 21 pm/°C at T ~ 400 °C.…”
Section: Nonresonant Micro/nanofiber Temperature Sensorsmentioning
confidence: 99%
“…However, this type of microfiber-attached structure is not steady, and the sensing approach is affected by various factors, including the stability of the microfiber structure, limited sensitivity and applications. Furthermore, extant studies examine temperature sensors by LPFG [34][35][36], although challenges persist, including achieving a simple structure, ease of fabrication and high precision.…”
Section: Introductionmentioning
confidence: 99%